Bronze beds. From hellenistic model to the Roman Cisalpine (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
The paper presents a general overview of a particular class and fine home furnishings such as beds decorated with bronze in the roman age. Starting from the hellenistic and greek models since their introduction in Rome, we focus on types and elements from which they then set up, to address the specific issues related to discovery of a bronze bed in Cisalpine. Exceptional objects s for completeness and achievement are the legs of bed tricliniar found in Modena in a rich domus of the city; such furniture, already the subject of reconstruction studies, are here examined particularly in the plastic scene which they decorated that has the image of Hercules against the Centaur. The hypothesis is that it can be a testimony to the propaganda images of Antonio in a particular juncture that the civil strife that affected the areas of northern Italy in the late Republic.
Keywords: Bed; bronze; fulcra; legs; applique; Cisalpine; furniture; triclinium; Heracles; Marcus Antonius